An evaluation of wrong-way driving crashes on Kansas freeways. - Cunningham, Jack R. IV (Kansas State University, 2017)
Transportation officials continuously seek to prevent and reduce wrong-way crashes on interstate highways in the United States. These crashes typically have a high probability of head-on vehicle crashes, resulting in fatalities or serious injuries due to excessive vehicle speeds, and decreased room to maneuver because of fixed barriers or rough shoulders. This research project studied wrong-way crashes on interstate highways in Kansas in order to determine what, if any, statistically significant variables contribute to wrong-way driving crashes. Although these crashes represented only 0.05 percent of all vehicle crashes in Kansas in 2015, wrong-way crashes were found to have a higher rate of fatalities and injuries. In Kansas, 22.6 percent of all crashes and 56 percent of all wrong-way crashes resulted in fatalities and injuries, even though typical vehicle crashes in Kansas occur at non-intersection locations in daylight or in the presence of streetlights without negative factors of adverse weather conditions or drivers influenced by alcohol or drugs. Using crash data provided by the Kansas Department of Transportation from the years 2005 to 2015, the research team examined 372 wrong-way crashes. A cumulative logit statistical model was developed to identify significant characteristics of variables associated with each wrong-way crash. Results showed that driver not under the influence of alcohol or drugs was a significant characteristic in fatal and injury wrong-way crashes. Additionally, certain days of the week were associated with decreased vehicle crash rates when compared to the reference category.
Keywords: Wrong-way driving; Transportation safety; Interstate highways; Freeways